Clostridium difficile and One Health. (July 2020) - Lim, S.C.; Knight, D.R.; Riley, T.V.
Abstract: Background: For over four decades, Clostridium difficile has been a significant enteric pathogen of humans. It is associated with the use of antimicrobials that generally disrupt the microbiota of the gastrointestinal tract. Previously, it was thought that C. difficile was primarily a hospital-acquired infection; however, with the emergence of community-associated cases, and whole-genome sequencing suggesting the majority of the hospital C. difficile infection (CDI) cases are genetically distinct from one another, there is compelling evidence that sources/reservoirs of C. difficile outside hospitals play a significant role in the transmission of CDI. Objectives: To review the 'One Health' aspects of CDI, focusing on how community sources/reservoirs might be acting as a conduit in the transfer of C. difficile between animals and humans. The importance of a One Health approach in managing CDI is discussed. Sources: A literature search was performed on PubMed and Web of Science for relevant papers published from 1 January 2000 to 10 July 2019. Content: We present evidence that demonstrates transmission of C. difficile in hospitals from asymptomatic carriers to symptomatic CDI patients. The source of colonization is most probably community reservoirs, such as foods and the environment, where toxigenic C. difficile strains have frequently been isolated. With high-resolution genomic sequencing, the transmission of C. difficile between animals and humans can be demonstrated, despite a clear epidemiological link often being absent. The ways in which C. difficile from animals and humans can disseminate through foods and the environment are discussed, and an interconnected transmission pathway for C. difficile involving food animals, humans and the environment is presented. Implications: Clostridium difficile is a well-established pathogen of both humans and animals that contaminates foods and the environment. To manage CDI, a One Health approach with the collaboration of clinicians, veterinarians, environmentalists and policy-makers is paramount.